Investigating the Shear Strength of New and Old Concrete Joints Under the Effect of Freezing and Thawing Cycles - Meysam Sadighi; Mohammad Ali Lotfollahi-Yaghin; Mohammad Naghavi (مجله مدل سازی در مهندسی)
In this article, in order to evaluate the shear strength at the junction of old and new concrete under successive cycles of freezing and thawing, for new concrete from three water-to-cement ratios of 0.4, 0.45 and 0.5 and bubble-making materials with values of 0, 0.1, 0.2, 0.3 and 0.4 percent by weight of cement used, as well as three grades of cement 300, 350 and 400 kg/m3 have been used and 300 consecutive cycles of thawing and freezing were applied after 3, 7 and 28 days of processing. The periods of thawing and freezing include lowering the temperature of the samples from 4°C to -18°C and raising it from -18°C to 4°C, which is done alternately and in a period of 4 hours for each thawing-freezing cycle. The samples were frozen for 3 hours and placed in water for 1 hour for the thawing process. The results of this research show that for the condition with and without the thawing and freezing cycle, the shear stress increases and decreases with the increase in the weight percentage of the bubble-making material, so that the amount of shear strength after applying the temperature cycle for the ratio of water to cement and different grades of cement, in the concrete sample with a processing time of 28 days and the bubble rate of 0 and 0.4 decreases on average by 93% and 18%, respectively, and the highest and lowest percentage of reduction in shear strength in different amounts of bubble-making material occurs in water-cement ratio of 0.5 and 0.45, respectively.